Dragon fruit versus soybean: impact on blood glucose of diabetic patients - Srywahyuni, Ade; Amelia, Dona; Merianti, Liza (Jurnal Keperawatan, 2023)
Introduction: Diabetes Mellitus (DM) is a severe problem with a rapidly increasing incidence rate. DM can affect almost all segments of society worldwide. The number of individuals with DM continues to rise yearly due to the sedentary lifestyle and unhealthy eating habits prevalent in contemporary society. Objectives: This study aims to compare the effects of soymilk and red dragon fruit consumption on fasting blood glucose levels in individuals with type 2 diabetes mellitus. Methods: The research design employed in this study is quasi-experimental with a pre-test-post-test approach involving two treatment groups. The study subjects were 54 individuals with type 2 diabetes mellitus from Bukittinggi. The participants were divided into three groups: an intervention group of 18 individuals who consumed red dragon fruit daily for seven days, a second intervention group of 18 individuals who consumed soymilk daily, and a control group of 18. Comparison analysis is done using the ANOVA test. Results: The research findings indicate that the p-value is 0.035, and the calculated t-value (2.198) is greater than the tabulated t-value (2.110. Furthermore, the consumption of red dragon fruit impacted fasting blood glucose levels and blood pressure, as evidenced by a p-value of 0.018 for fasting blood glucose and a calculated t-value of 2.198, which exceeds the tabulated t-value of 2.110. The ANOVA results indicate that the effectiveness of red dragon fruit consumption is superior, with an average decrease in blood glucose levels of 32.56, compared to the effectiveness of soymilk consumption, which resulted in an average decrease of 22.50. Conclusions: Red dragon fruit is more effective in reducing blood glucose and blood pressure levels in patients with type 2 diabetes mellitus.